Computer-Controlled Detonation Spraying: Flexible Control of the Coating Chemistry and Microstructure - Vladimir Yu. Ulianitsky (Metals, 2019)
This article is a focused review aimed to describe the potential of the computer-controlled detonation spraying (CCDS) for producing and designing coatings with variable chemical and phase compositions and microstructure and promising properties. The development of the detonation spraying method is briefly analyzed from a historical perspective and the capabilities of the state-of-the art facilities are presented. A key advantage of the CCDS is the possibility of using precisely measured quantities of the explosive gaseous mixtures for each shot of the detonation gun and different oxygen to fuel ratios, which can create spraying environments of different chemical properties—from severely oxidizing to highly reducing. The significance of careful adjustment of the spraying parameters is shown using material systems that are chemically sensitive to the composition of the spraying environment and temperature. Research performed by the authors on CCDS of different materials—metals, ceramics, intermetallics and metal-ceramic composites is reviewed. Novel applications of detonation spraying using the CCDS technology are described.